Analisis Prinsip dan Peran Asesmen Autentik pada Proses dan Hasil Belajar Peserta Didik - Ester Novi Kurnia Zebua; Nofamataro Zebua (Lembaga Pengembangan Kinerja Dosen, 2024)
Education is a planned effort to create an ideal learning environment. The learning and assessment process is an integral part of achieving basic competencies in the curriculum. However, traditional measurements such as national exams do not always reflect students' talents and the actual quality of education. This article proposes the use of authentic assessment as a solution to measure real student learning outcomes, which also reveal students' real abilities that can be applied in real life. This research uses a descriptive qualitative approach and source triangulation techniques to evaluate the principles and role of authentic assessment in learning. Authentic assessment principles include holistic measurement and various aspects of learning, as well as using various methods and sources. Authentic assessment plays an important role in improving the teaching-learning process and improving student learning outcomes by encouraging conceptual understanding, problem solving, and application of knowledge in real contexts. Additionally, authentic assessments provide feedback that allows students to improve the quality of their learning. Authentic assessment is expected to change the educational paradigm to be more student-oriented and increase the relevance of learning to real life.